INTEGRATING AI IN EDUCATIONAL GAME DESIGN: A ROBLOX-BASED APPROACH TO PRESERVING SUNDANESE TRADITIONS FOR YOUNG LEARNERS - Karlina, Nichi Hana; Indarta Priyana; Diwan Setiawan; Citra Kemala Putri; Shinta Hartini Putri; Hengky (Telkom University, 2025)
This study aims to design a conceptual framework for an educational game based on the Roblox platform that integrates Artificial Intelligence (AI) technology to support the preservation of Sundanese culture among children aged 6–10 years. In today's digital era, children are more attracted to interactive media and have limited exposure to local cultural values. Therefore, adaptive learning and Natural Language Processing (NLP) approaches are utilized to create a personalized and communicative learning experience. This research employs a descriptive qualitative approach, with data collected through literature review, observation of Roblox content, and analysis of Sundanese cultural elements. The findings indicate that integrating AI into culturally-based educational games holds significant potential to enhance children's engagement in learning local culture in a contextual and enjoyable manner.